Afghanistan : Country Gender Assessment, National Reconstruction and Poverty Reduction, the Role of Women in Afghanistan's Future - World Bank (Washington, DC, 2012)
Throughout the 20th century, the debate on women's rights and their role in Afghan society has been closely interlinked with the national destiny. Women not only carry the burden of symbolizing the honor of the family, but often are seen as embodying the national honor as well. Gender has thus been one of the most politicized issues in Afghanistan over the past 100 years, and attempts at reform have been denounced by opponents as un-Islamic and a challenge to the sanctity of the faith and family. During the years of turmoil, concerns about women's security led to the imposition of ever-stricter interpretations of socially acceptable female behavior, supported by the most conservative reading of the holy scriptures. Despite the rhetoric, women suffered from very serious human rights violations throughout the conflict. With the overthrow of the Taliban regime in 2001, Afghanistan embarked upon a new beginning, recognizing anew the contribution of the female half of its society. This Country Gender Assessment report identifies critical areas in which gender-responsive actions are likely to enhance growth, poverty reduction and human well-being. The extent of gender discrimination in Afghanistan is pervasive, and the present report focuses on a few key sectors deemed particularly important for both short- and long-term interventions. Gender gaps are widespread in health, education, access to and control over resources, economic opportunities and power and political voice, and while women and girls bear the direct cost of these inequalities, the negative effects are felt throughout society. This report makes the case that improvements in women's situation are essential for the reconstruction of the country - and that sizable investments in this regard will yield large benefits.